1999
DOI: 10.1093/molehr/5.8.757
|View full text |Cite
|
Sign up to set email alerts
|

Localization of regulatory protein binding sites in the proximal region of human myometrial connexin 43 gene

Abstract: Parturition is preceded by a large increase in gap junctions between myometrial smooth muscle cells. Connexin 43 is the major structural protein of myometrial gap junctions. To explore transcriptional regulation of the myometrial Cx43 gene, we used DNase I footprinting, electrophoretic mobility shift and transient transfection assays to examine a 312 bp promoter region (-164 to +148) of the gene, utilizing human myometrial cell cultures and nuclear extracts. The DNase I studies showed four regions of nucleopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 48 publications
8
44
0
Order By: Relevance
“…The promoter region of CX43 contains NFkB binding sites, suggesting that NFkB activation can stimulate CX43 expression (Echetebu et al 1999). In this study, we found that NFkB signalling was involved in CX43 expression.…”
Section: Discussionmentioning
confidence: 55%
“…The promoter region of CX43 contains NFkB binding sites, suggesting that NFkB activation can stimulate CX43 expression (Echetebu et al 1999). In this study, we found that NFkB signalling was involved in CX43 expression.…”
Section: Discussionmentioning
confidence: 55%
“…Interestingly, activation of activator protein-1, a well characterized downstream target of JNK, has been shown to be necessary for maximal Cx43 promoter activity in human myometrial smooth muscle. 39 In addition, aortic smooth muscle cells have been shown to significantly increase steady-state levels of Cx43 mRNA in response to hypertension, 40 a known activator of JNK. 41 Together, these experiments suggest that the Cx43 promoter is subject to JNK-mediated regulation in a cell-type-specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Therefore, we wanted to examine if stretch induces nuclear accumulation of these transcription factors. In our EMSA experiments enhanced localization of both factors in the nuclei of stretched cells could clearly be demonstrated and, because previous studies of our working group indicated a dependence of Cx43 expression on nuclear presence of AP1 and CREB after ERK1/2 activation by isoprenaline, 33 it might be possible that these transcription factors are upregulated following ERK1/2 activation by stretch.…”
Section: Salameh Et Al Stretch and Cardiac Gap Junction Localizationmentioning
confidence: 99%